What explains differences in foreclosure rates? A response to Piskorski, Seru, and Vig - Manuel Adelino; Kristopher Gerardi; Paul Willen (Federal Reserve Bank of Boston, 2010)
In this note we discuss the findings in Piskorski, Seru, and Vig (2010), as well as the authors; interpretation of their results. First, we find that small changes to the set of covariates used by PSV significantly reduce the magnitude of the differences in foreclosure rates between securitized and nonsecuritzed loans. Second, we argue that early payment defaults (EPD) are not a valid instrument for the securitization status of the loans and that the empirical implementation chosen by the authors for using EPD is not a valid instrumental variables approach. Finally, we discuss the use of foreclosure rates as a measure of renegotiation and argue that explicitly using modification rates of delinquent mortgages is a better way of studying renegotiation activity. On balance, the evidence in PSV indicates that there are at most small differences in the outcomes of delinquent loans, but whether those differences reflect accounting issues, willingness to renegotiate, or unobserved heterogeneity remains an open question.
Keywords: D11; D12; G21; 330